Effectiveness of breathing exercises, foot reflexology and massage (BRM) on maternal and newborn outcomes among primigravidae in Saudi Arabia: a randomized controlled trial - Baljon, Kamilya; Romli, Muhammad Hibatullah; Ismail, Adibah Hanim; Lee, Khuan; Boon, How Chew (Dove Press, 2022)
Background: Labor pain and anxiety are important concerns during labor, especially among the primigravidae. It may increase the duration of labor, increase stress hormones, and affect maternal and new-born related outcomes. This study examined the effectiveness of combined breathing exercises, foot reflexology, and massage (BRM) interventions on labor pain, anxiety, labor duration, stress hormone levels, maternal satisfaction, maternal vital signs, and the new-born’s APGAR scores. Participants and Methods: This single-blind-parallel randomized controlled trial (RCT) was conducted at the Maternity and Children Hospital (MCH), Makkah, Saudi Arabia, by recruiting primigravidae aged 20 to 35 years, without any medical complications, and who were block-randomized at six-centimeter cervical dilation and stratified by intramuscular pethidine. The intervention is BRM compared to standard care. The labor pain was measured via present behavioral intensity (PBI) and visual analogue scale (VAS), and the anxiety was measured via Anxiety Assessment Scale for Pregnant Women in Labor (AASPWL). The secondary outcomes were duration of labor, maternal stress hormone levels, maternal vital signs, maternal satisfaction, fetal heart rate, and APGAR scores. All outcomes were measured at multiple time-points during and after contraction at baseline, during BRM intervention, at 60, 120, and 180 minutes post-intervention. Generalized linear mixed models were used to estimate the intervention effects over time. Results: A total of 225 participants were randomized for the control (n = 112) and intervention group (113). BRM lowered the labor pain intensity at 60 minutes after intervention during (1.3 vs 3.5, F = 102.5, p < 0.001) and after contraction (0.4 vs 2.4, F = 63.6, p < 0.001) and also lowered anxiety (2.9 vs 4.2, F = 80.4, p < 0.001). BRM correspondingly lowered adrenocorticotropic (ACTH) (133 vs 209 pg/mL, p < 0.001), cortisol (1231 vs 1360 nmol/mL, p = 0.003), and oxytocin (159 vs 121 pg/mL, p < 0.001). It also shortened the labor duration (165 vs 333 minutes, p < 0.001), improved vital signs, which resulted in higher APGAR scores, and increased maternal satisfaction. Conclusion: The labor unit management could consider adopting BRM as one of the non-pharmacological analgesia for healthy women in labor.